A review on the benefits of horticultural theraphy for retirement community in Malaysia / Amirul Amin Ismail ... [et al.] - Amirul Amin, Ismail; Ismail, Samsuddin; Azman, Zainonabidin; Harlina, Mohd Ali (Universiti Teknologi MARA, Perak, 2017)
By the year 2030, Malaysian population will experience the after effects of the rapid growth of ageing society. This paper investigates the impact of seamless integration pd horticultural activity in the new residential typology of retirement community. It is believed that the horticultural is not only beneficial for physical and psychological but also promotes socialisation oppotunities among the elderly. Comparative analysis methods on selected precedent studies has been carried out and analysedin accordance with Malaysian context. Initial findings indicate that a retirement community with horticultural gives theraphy for healthier well-being. This therapeutic can be a positive change in elderly lifestyle and essential towards the establishment of retirement community in Malaysia.